PHYSIOLOGY OF CARDIOMYOCYTES - o‘g‘li, Isomiddinov Humoyunxon G‘ovsiddin (Research Focus International Scientific Journal, 2026)
This article examines human embryology, focusing on the developmental processes from fertilization to birth. The stages of embryo formation, including cell division gastrulation, and organogenesis, are analyzed from a scientific perspective. The study also highlights the importance of embryology in medicine, particularly in detecting congenital abnormalities, preventing developmental disorders, and ensuring the formation of a healthy generation.